A panel of miRNAs derived from plasma extracellular vesicles as novel diagnostic biomarkers of lung adenocarcinoma - Bing Yao; Shuang Qu; Ruifeng Hu; Wen Gao; Shidai Jin; Ming Liu; Quan Zhao (FEBS Open Bio)
Lung cancer is the leading cause of cancer‐related morbidity and mortality worldwide, with lung adenocarcinoma (LUAD) being the most common histological subtype (approximately 40%). In the absence of reliable screening biomarkers for early diagnosis, most patients with LUAD are inevitably diagnosed at an advanced stage. MicroRNAs (miRNAs) encapsulated within plasma‐derived extracellular vesicles (EVs) may be suitable for use as noninvasive diagnostic biomarkers for aggressive malignancies, including LUAD. In this study, we first investigated the miRNA profiles of plasma‐derived EVs from LUAD patients and healthy donors, and then systematically evaluated the expression patterns of selected plasma‐derived EV miRNAs in a large cohort of patients with LUAD and healthy controls. Notably, we observed that miR‐451a, miR‐194‐5p, and miR‐486‐5p were significantly increased in EVs from LUAD patients, compared to healthy controls. The area under the curve values for the three miRNAs were 0.9040 (95% confidence interval [CI], 0.8633–0.9447) for miR‐451a, 0.7492 (95% CI, 0.6992–0.7992) for miR‐194‐5p, and 0.9574 (95% CI, 0.9378–0.9769) for miR‐486‐5p, while the AUC of the combination of these three miRNAs was 0.9650. Thus, these results suggest that these EV miRNAs may be promising candidates for the development of highly effective, noninvasive biomarkers for early LUAD diagnosis.